Highly active bidirectional electron transfer by a self-assembled electroactive reduced-graphene-oxide-hybridized biofilm - Yong, Yang-Chun (2014)
Low extracellular electron transfer performance is often a bottleneck in developing high-performance bioelectrochemical systems. Herein, we show that the self-assembly of graphene oxide and Shewanella oneidensis MR-1 formed an electroactive, reduced-graphene-oxide-hybridized, three-dimensional macroporous biofilm, which enabled highly efficient bidirectional electron transfers between Shewanella and electrodes owing to high biomass incorporation and enhanced direct contact-based extracellular electron transfer. This 3D electroactive biofilm delivered a 25-fold increase in the outward current (oxidation current, electron flux from bacteria to electrodes) and 74-fold increase in the inward current (reduction current, electron flux from electrodes to bacteria) over that of the naturally occurring biofilms.